Penerapan Komputer Dalam Mengidentifikasi Virus dan Bakteri Penyakit Ichtyosis Menerapkan Algoritma Rete - Thomas Sanjaya (Journal of Pharmaceutical and Health Research, 2020)
Most people use it not only for commercial purposes, but also to obtain information on the detection of diseases quickly and efficiently with computer-based applications that can help the general public to find out the causes and symptoms of the disease. For this reason, we need a system designed to be able to imitate the expertise of an expert in answering questions and solving a problem in accordance with the knowledge of an expert that is entered into a computer system. The development of artificial intelligence technology that occurred has enabled expert systems to be applied in detecting diseases using programming languages. One of them is in providing information about various problems, especially hepatitis. The expert system method used is the Rete Algorithm used to deal with uncertainty in the diagnosis of ichthyosis. With the facilities provided for the user, allowing users to use this system according to their individual needs. Users are given the ease of knowing information about the symptoms of ichthyosis, and its prevention.